CUSTOMERS’ EXPECTATIONS AND PERCEPTION TOWARDS SATISFACTION OF HOTELS’ SERVICE QUALITY IN PATTAYA CITY, CHONBURI PROVINCE - Kunlaya Sroysing, กัลยา สร้อยสิงห์ (Dusit Thani College Journal, 2018)
The purposes of this research were to study the level of expectations and perception towards customer service quality, to compare of expectations and perception towards customer service quality and to evaluate satisfaction with the service quality of customers of the Hotels in Pattaya City, Chonburi. The sample consisted of 400 customers who had received service. The tool used for collecting data was questionnaire which included Personal data, Expectations and Perception. The data were analyzed with several statistical techniques such as Percentage, Mean, Standard Deviation, and Paired sample t – test. The research revealed that: 1) Expectations of customers towards overall service quality were at the high level while perception of customers towards overall service quality were at the highest level too. 2) The difference of expectations and perception of customers towards service quality was statistically significant at 0.05. 3) The customers were satisfied with the service quality. The average perception was higher than the average expectation towards service quality.